Advantageous Role of N-doping on K@Al in COS/CS2 Hydrolysis: Diminished Oxygen Mobility and Rich basic sites. (1st April 2023) - Cao, Rui; Wang, Xueqian; Ning, Ping; Xie, Yibing; Wang, Langlang; Ma, Yixing; Li, Xiang; Zhang, Hui; Liu, Jingye
Highlights: The N -doped alumina-based catalyst lowered the temperature of simultaneous COS/CS2 hydrolysis to 160 °C. The strong interaction between nitrogen and potassium reduces the reactive oxygen density. The introduction of pyridine nitrogen significantly enhanced the basic sites on the catalyst. N -doping reduces the adsorption performance of H2 S on the catalyst. Bicarbonate and thiocarbonate are the main intermediates of the hydrolysis reaction. Abstract: Basic sites are important to promote carbonyl sulfide (COS) and carbon disulfide (CS2 ) hydrolysis activity while improving the oxidation resistance of hydrolysis catalysts is a challenge. Here, we report an N -doped alumina-based catalyst ( N -K@Al), where the complete hydrolysis removal of COS and CS2 by the N -doped catalyst was extended up to 15 h at 160 °C, and the turnover frequency (TOF) value of the catalyst was increased from 0.85 × 10 -2 s −1 to 1.16 × 10 -2 s −1 . The results showed that the strong interaction between nitrogen and potassium decreased the reactive oxygen density and activated –OH, weakening the oxygen mobility. In addition, the beneficial effects of N -doped included the addition of moderately and weakly basic sites by pyridine N. The optimized N -K@Al showed good catalytic performance in the hydrolysis of COS and CS2 removal with lower reaction temperature and higher total hydrogen sulfide yield. Density functional theory calculations revealed that N -K@Al reduced the Gibbs free energy of COS and CS2 hydrolysis to 0.21 eV and 0.33 eV, respectively, contributing to the enhanced catalytic activity. The present study presents new strategies for developing efficient antioxidant organosulfur hydrolyzers and other practical industries.